(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Vaishvanara Churna is an Ayurvedic polyherbal formulation used traditionally as a Saraka (laxative), Shotaprasamana (anti-inflammatory) and for the treatment of Amavata (Rheumatoid Arthritis), management of Vibandha (Constipation), Udaravedana (abdominal pain), and Hridroga (heart disease). All the ingredients used in Ayurvedic formulations are of natural origin, owing to which the standardization of Ayurvedic formulations is difficult, which is the need of the hour. Vaishvanara Churna is one such Ayurvedic formulation. The Ayurvedic and other traditional systems of medicines are effective in curing several ailments, but the problem with them is they lack in satisfying quality assurance and quality control parameters, which help us recognize the quality of the formulation. Reliable clinical study data is not available, which thereby increases the scope of research in this area of medicine. This article aims at defining standards by comparing different marketed formulations and an in-house formulation for the evaluation of Vaishvanara Churna. Our study basically intends to highlight the variations observed in marketed samples of Ayurveda formulations, using Vaishvanara Churna as an example. It is an unbiased study and have no intentions to claim anyone of the samples is superior to the other. The Churna was evaluated for its pharmacognostic, pharmaceutical and microbial parameters. The results obtained were within the limits prescribed by Ayurvedic Pharmacopoeia.